Contrasting paired benthic and planktonic foraminifera radiocarbon ages from Bermuda Rise ODP Site 1063 during Heinrich Stadials 1 and 2 - Lippold, Jörg; Fohlmeister, Jens; Wacker, Lukas; Kucera, Michal; Kromer, Bernd; Grützner, Jens (Radiocarbon, 2024)
We report 27 planktonic and 21 benthic radiocarbon ages from the subtropical marine sediment core ODP Site 1063 (Bermuda Rise) for the time range between 30 and 14 ka before present. Despite low abundances of benthic specimens, it was possible to measure radiocarbon ages down to ∼10 µg carbon using a MICADAS and the gas ion source developed at ETH Zurich. Based on a tentative radiocarbon-independent age-model we found that the radiocarbon reservoir of the bottom water varied moderately relative to the analytical and age-model related uncertainties throughout the examined time-period, but larger differences in the radiocarbon reservoir appear to have affected the upper ocean layer. In particular, radiocarbon levels around Heinrich Stadial 2 reveal surface radiocarbon content similar to that of the atmosphere, while during Heinrich Stadial 1 surface waters were significantly depleted in 14C.
Gesehen am 20.05.2025